HER2 testing in metastatic breast cancer – is reflex in situ hybridization necessary in cases that are equivocal by immunohistochemistry?. (28th October 2021) - Liwski, C R; Castonguay, M; Barnes, P; Bethune, G; Rayson, D
Abstract: Introduction/Objective: Current guidelines recommend HER2 testing on all primary invasive breast cancers and at least one metastatic lesion. Typical HER2 testing involves immunohistochemistry (IHC), with reflex in situ hybridization (ISH) in the event of equivocal (2+) IHC. ISH testing is time consuming and resource intensive, and there may be situations where it is unnecessary. The incidence of discordance between HER2 negative primary tumors and HER2 IHC2+ metastases that are ISH positive is unknown. We hypothesize that the majority of such cases are non- amplified. Methods/Case Report: A retrospective review of IHC2+ metastatic lesions further assessed with ISH at our center from 2013-2021 was undertaken. A total of 105 cases were identified after exclusion of cases missing HER2 results, with primaries of unconfirmed origin, and cases of synchronous primary and metastatic disease. IHC and ISH results were recorded, with a detailed slide review of discordant cases. Results (if a Case Study enter NA): 91/105 metastases had HER2 negative primaries (87%). A metastasis was significantly more likely to be HER2 negative when the primary was HER2 negative (93%) versus positive (43%) (p < 0.0001). 54/91 primaries were IHC2+/ISH negative, and 50/54 (93%) corresponding metastases had identical results. Of the 37 HER2 negative primaries that were IHC0/1+, 35 (95%) corresponding metastatic tumors were ISH negative. Six metastatic lesions in cases with HER2 negative primaries were discordant and slides were reviewed. Characteristics of metastatic tumors suggesting ISH testing was warranted to assess for discordance included IHC heterogeneity, morphological discordance, and increased staining of moderate intensity. These factors were present in all six discordant metastases. Conclusion: Our results suggest that selective rather than reflex ISH testing on HER2 IHC2+ breast cancer metastases in the context of HER2 negative primary disease may be appropriate when there is careful review of the IHC. Validation of our findings await further studies with larger sample sizes.